Strategic Alliance-Case Study of Lenovo and IBM - Jiang, Lili (2007)
Strategic alliance gains high popularity in recent decades and has become an increasingly favorable choice for the company that intends to attain a competitive edge over other rivals so as to make a stand in the global market. Facing with the rapid globalization trend and dramatic economic development, it is almost impossible for any companies to develop individually, just as Doz and Hamel (1998) argue that in this new world, networks, coalitions, alliances, and strategic partnerships are not an option but a necessity for companies to achieve competitive success.